Tribes : we need you to lead us - Godin, Seth (Portfolio, 2008)
According to Godin, Tribes are groups of people aligned around an idea, connected to a leader and to each other. Tribes make our world work, and always have. The new opportunity is that it's easier than ever to find, organize, and lead a tribe. The Web has enabled an explosion of all kinds of tribes--and created shortage of people to lead them. This is the growth industry of our time. Tribes (the book) will help you understand exactly what's at stake, and why you can and should lead a tribe of your own.